2008
DOI: 10.1182/blood-2007-09-113092
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle–dependent chromatin loading of the Fanconi anemia core complex by FANCM/FAAP24

Abstract: IntroductionThe 13 identified Fanconi anemia (FA) proteins cooperate in a common cellular pathway regulating the cellular response to DNA cross-linking agents, such as cisplatin (CDDP), diepoxybutane (DEB), and mitomycin C (MMC). 1 Of these FA proteins, 8 (A, B, C, E, F, G, L, and M) are assembled into a core complex, 2,3 which contains a ubiquitin E3 ligase activity (FANCL subunit) 4 and a DNA translocase activity (FANCM). 5 In response to DNA damage, or during S-phase progression, the FA core complex coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
176
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(189 citation statements)
references
References 38 publications
12
176
0
1
Order By: Relevance
“…xFANCM Is a Chromatin-binding Phosphoprotein-Recent studies showed that human FANCM binds to chromatin and is phosphorylated during the S phase of the cell cycle and in response to DNA-damaging agents like mitomycin C or hydroxyurea (8,12). To analyze xFANCM chromatin recruitment during a synchronous S phase, we incubated Xenopus sperm chromatin in egg extracts that allow for nuclear assembly and DNA replication under natural cell cycle control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…xFANCM Is a Chromatin-binding Phosphoprotein-Recent studies showed that human FANCM binds to chromatin and is phosphorylated during the S phase of the cell cycle and in response to DNA-damaging agents like mitomycin C or hydroxyurea (8,12). To analyze xFANCM chromatin recruitment during a synchronous S phase, we incubated Xenopus sperm chromatin in egg extracts that allow for nuclear assembly and DNA replication under natural cell cycle control.…”
Section: Resultsmentioning
confidence: 99%
“…In human cells, FANCM localizes to chromatin and is required for chromatin recruitment of other FA core complex proteins (8,12). FANCM is phosphorylated during both the M and S phases and in response to DNA-damaging agents (8,12,13). Interestingly, DNA damage-induced phosphorylation of FANCM is independent of the FA core complex (8), suggesting that FANCM is controlled by other, as yet unknown upstream components of the DNA damage response.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Another two of these proteins, FANCD2 (at K561) and FANCI (at K523), collectively referred to as ID2, are monoubiquitylated in response to ICL (Table 2), which is detected on the basis of the association of FANCM with a stalled replication fork in S phase (Kim et al . 2008). FANCL contains a RING finger domain and is the catalytic subunit of the FA core complex.…”
Section: Regulation Of Dna Damage Repair and Dna Replication By Monoumentioning
confidence: 99%
“…Entretanto, enquanto o reparo por HR demora aproximadamente sete horas, o reparo por NHEJ demora em média trinta minutos (Mao et al, 2008) (Räschle et al, 2008). O reparo dessas lesões é iniciado pelo reconhecimento da lesão, através da parada na forquilha de replicação, pela proteína FANCM (Kim et al, 2008) (Wu e Hickson, 2003). As proteínas BRCA1 e BRCA2 (FANCD1) também são recrutadas pelas proteínas FANC (Garcia-Higuera et al, 2001) e estão envolvidas na coordenação dos processos de reparo por recombinação necessários para a estabilização da forquilha bloqueada e continuação do reparo na fase S, também dependentes de RAD51 e das polimerases REV1 (Mirchandani et al, 2008),  (Moldovan et al, 2010) e  (REV7/REV3L).…”
Section: Reparo Diretounclassified